A 2013 Social Accounting Matrix for Zimbabwe - Robert H. Davies; Marko Kwaramba; Dirk Ernst van Seventer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper documents the construction of a Social Accounting Matrix (SAM) for Zimbabwe in 2013. The SAM was built using National Accounts data from the Zimbabwe National Statistics Agency (ZIMSTAT), including balance of payment data, government finance data, and highly aggregated industry-level production accounts. Detailed data on industry and service sectors were obtained from ZIMSTAT surveys. For some activities, unpublished but recent supply and use data on disaggregated industries were combined with data from older sources. These sources include a 2011/12 ZIMSTAT household survey, trade data, the Central Government Budget, and output and price data from private farming organizations. The SAM provides a detailed representation of Zimbabwe's economy with 36 activities and 48 commodities. The SAM disaggregates labour into skilled and unskilled labour and separates households into rural and urban households. Despite shortcomings in the underlying data, it is hoped that this initial attempt at constructing a SAM representing the economy of Zimbabwe after land reform will stimulate further work aimed at improving it.
Keywords: C63; E01; E16; 330; Social Accounting Matrix; National Accounts; supply table; use table; Zimbabwe